TAREKAT NAQSYABANDIYAH SYAIKH ABDUL WAHAB ROKAN: Sejarah, Ajaran, Amalan, dan Dinamika Perubahan - L. Hidayat Siregar (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2011)
Abstract:Tarekat Naqsyabandiyah Syaikh Abdul Wahab Rokan: history, teachings, practice and its dynamics of change. The Tarekat Naqsyabandiyah in North Sumatra was first developed by Syaikh Abdul Wahab Rokan. In reality, such teaching of tarekat developed by him has changed the lives of its followers in Babussalam socially to a more prosperous course. In this article, the writer traces the history, teaching and practice of tarekat Naqsyabandiyah Syaikh Abdul Wahab Rokan in Babussalam as well as analyzes the dynamics of change there in. The author argues that the application of the teaching of tarekat Naqsyabandiyah Syaikh Abdul Wahab Rokan which emphasizes that the material world is not the only matter in life has become an avenue for creating a balance between the profane and eternal dimensions of life.Kata Kunci: Tarekat, Naqsyabandiyah, Syaikh Abdul Wahab Rokan